Photo-Driven Highly Efficient One-Step CO2 Biomethanation with Engineered Photo-Synthetic Bacteria Rhodopseudomonas palustris - Ma, Liqin; Fang, Zhen; Wang, Yan-Zhai; Zhou, Jun; Yong, Yang-Chun (ACS sustainable chemistry & engineering, 2020)
CO2 methanation is considered as a promising process for methane production and renewable energy storage. However, current methane production processes involve nonrenewable energy input or high temperature and pressure, which raises the concerns of sustainability. Here, a sustainable photo-driven one-step CO2 biomethanation approach using whole-cell biocatalysis was established by endowing the methanation capability to a photosynthetic bacterium (PSB). With simple genetic engineering of inherent dinitrogen reductase, the CO2 biomethanation PSB was constructed from facultative anaerobic bacteria of Rhodopseudomonas palustris CGMCC 1.2180. With this engineered PSB strain, one-step CO2 biomethanation powered by sustainable solar energy was realized at ambient temperature and pressure. After optimization, a record-high photo-driven bio-CH4 yield (CO2-to-CH4, 35% with 10 μmol/L CO2) was achieved. This study provided an efficient and sustainable methane-producing approach, demonstrating the great potential of bacterial methanation for CO2 transformation and solar energy harvesting.